2013
DOI: 10.3741/jkwra.2013.46.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Drought Risk Analysis Using Stochastic Rainfall Generation Model and Copula Functions

Abstract: This study performed the bivariate drought frequency analysis for duration and severity of drought, using copula functions which allow considering the correlation structure of joint features of drought. We suggested the confidence intervals of duration-severity-frequency (DSF) curves for the given drought duration using stochastic scheme of monthly rainfall generation for 57 sites in Korea. This study also investigated drought risk via illustrating the largest drought events on record over 50 and 100 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Madadgar and Moradkhani [25] showed that the Gaussian copula is the most suitable for forecasting the flow of the Gunnison River in the United States. Yoo et al [27] used a copula function on Korean weather observatories and performed bivariate frequency analyses for droughts. They presented results showing that the Gaussian copula was the most suitable for the data from 32 of the 57 target weather observatories.…”
Section: Copula-based Bayesian Networkmentioning
confidence: 99%
“…Madadgar and Moradkhani [25] showed that the Gaussian copula is the most suitable for forecasting the flow of the Gunnison River in the United States. Yoo et al [27] used a copula function on Korean weather observatories and performed bivariate frequency analyses for droughts. They presented results showing that the Gaussian copula was the most suitable for the data from 32 of the 57 target weather observatories.…”
Section: Copula-based Bayesian Networkmentioning
confidence: 99%
“…However, due to the ambiguity in delineating its onset and termination, various methodologies are possible to establish clear thresholds based on rainfall or river runoff. In the assessment of meteorological drought, researchers have pursued univariate low flow frequency analysis predicated on precipitation data [1][2][3]. Univariate low flow frequency analysis, utilizing precipitation as its primary variable, involves establishing a baseline precipitation level to ascertain both the duration and magnitude of the low flow event.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, research on multivariate frequency analysis has predominantly utilized the copula model, as evidenced by studies conducted by [1][2][3]8]. Within the framework of the copula model, the interrelation among various low flow factors in a low flow frequency analysis can be encapsulated and elucidated through the copula function.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2017) (Dai et al,. 1998;Cook et al, 1999;Hisdal and Tallaksen, 2003;Kim et al, 2006;Kyoung et al, 2007;Ganguli and Reddy, 2012;Yoo et al, 2013;Halwatura et al, 2015;Yoo et al, 2015;Yu et al, 2016). 최근에는 3차원 시공간적 해석을 사용하여 가뭄을 특성화하려는 연구가 진행되고 있다 (Sheffield et al, 2009;Wang et al, 2011;Xu et al, 2015;Liu et al, 2019…”
unclassified